Impacts of Capital Formation, Labor, Human Development, and Tourism on Economic Growth in Yogyakarta Province - Zulaekha Setiyani; Jihad Lukis Panjawa; Jalu Aji Prakoso; Yustirania Septiani (Universitas Airlangga, 2025)
Objective: This study investigates the determinants of regional economic growth in the Special Region of Yogyakarta, focusing on five districts and cities during the period 2011–2024. The research addresses the problem of persistent interdistrict disparities despite Yogyakarta’s consistently higher economic growth than the national average. The main objective is to identify the key factors influencing regional growth and to assess their relative contributions within a tourism-driven economy. This empirical research is relevant to the broader macroeconomic context of regional development and income distribution. Methods: An empirical analysis using static panel data regression with a Fixed Effect Model (FEM) is employed. The dataset covers annual observations from 2011 to 2024 for five administrative areas. Variables include Gross Fixed Capital Formation (GFCF), the Human Development Index (HDI), labor force participation, and tourism income. The FEM method effectively controls for regional and temporal heterogeneity, yielding robust estimates of growth determinants. Findings: Empirical results reveal that GFCF, HDI, and tourism income have significant, positive effects on regional economic growth, underscoring the importance of investment, human capital, and tourism as primary drivers of growth. Conversely, the labor force variable shows no statistically significant impact. These findings underscore the distinct structure of Yogyakarta’s economy, where capital formation and tourism-based income play a more dominant role than labor quantity in driving growth. Originality/Value: This study enriches existing literature by reassessing growth determinants using updated data and emphasizing Yogyakarta’s tourism-based regional economy. It fills gaps in prior studies marked by mixed findings and limited tourism-focused analyses, offering new empirical insights into the tourism growth nexus at the subnational level. Policy Implication: Findings suggest that local governments should strengthen investment, human capital, and tourism development to achieve inclusive and sustainable growth. Policy efforts focusing on infrastructure, education, and tourism promotion are essential to reducing interdistrict disparities and fostering balanced regional development.